Associations between the SMARS score derived from CT and MRI with histopathological features in HCC - Daniele Romeo; Theresa Richter; Anne-Kathrin Höhn; Hans-Michael Tautenhahn; Daniel Seehofer; Uwe Scheuermann; Timm Denecke; Hans-Jonas Meyer (Scientific Reports)
Abstract There are complex associations between the imaging phenotype and underlying histopathology of hepatocellular carcinomas (HCC). The recently proposed SMARS score (acronym comprising Shape of tumour, Mosaic architecture, AFP level, Rim APHE, and Satellite lesion) could discriminate proliferative and non-proliferative HCC tumours in a non-invasive way and was associated with treatment outcomes. However, a systematic validation of this score is needed and it is unclear whether associations with histopathology features exist. The present study elucidates possible correlations between the SMARS score defined by CT and MRI images with immunohistochemistry features of the pathological specimens in a curatively treated HCC cohort. A total of 44 patients (mean age: 59.6 ± 10.7 years) with histologically confirmed HCC, who underwent curative surgical resection, were included in the present analysis. Contrast enhanced MRI and CT images were performed before surgery and the SMARS score was calculated. The pathological specimens were analyzed for programmed death ligand 1 (PD-L1), Glypican-3, CD3-tumour infiltrating lymphocyte, CD68 positive cells, CD34 positive microvessel density (MVD). The median SMARS score derived from MRI images was 1.4 (interquartile range: -0.32; 2.18) and from CT images it was − 0.32 (interquartile range: -1.08; 0.56). According to the proposed threshold, 29 tumours were categorized as proliferative HCC (82.9%) and six tumours as nonproliferative HCC (17.1%) accordingly to the MRI SMARS score. According to the CT SMARS score 24 tumours were categorized as proliferative HCC (61.5%) and 15 as nonproliferative HCC (38.5%). The SMARS score derived from MRI images showed no correlations with the PD-L1, CD68, CD3 and MVD parameters. However, a moderate association was shown between the SMARS score with the Glypican-3 expression (r = 0.37, p = 0.03). The SMARS score derived from CT images, instead, showed correlations with two of the PD-L1 parameters (for PD-L1 tumour positive score r=-0.37, p = 0.02 and for PD-L1 combined positive score r=-0.35, p = 0.03) while no other association with the remaining parameters was detected. The SMARS score as a promising novel imaging score is associated with the Glypican-3 and PD-L1 expression in curatively treated HCC patients. Differences between the CT and MRI defined score needs to be investigated in further trials on larger patient cohorts.